Prostaglandins from human T suppressor/cytotoxic cells modulate natural killer antibacterial activity (The Rockefeller University Press, 1989)
We have recently described potent antibacterial activity of purified human NK cells. Here we show that this function is regulated by T cytotoxic/suppressor CD8+ cells. Thus, coculture of NK and CD8+ cells for 3 h or longer times abrogated the expression of the NK antibacterial activity, and of two activation markers IL-2R and transferrin receptor (Tf-R). The suppressive activity was mediated by PGE2 as demonstrated by direct PGE2 determination in CD8+ cell free supernatants, and by inhibition of CD8+ cell suppression with indomethacin or piroxicam in vitro. We also found that resting T cytotoxic/suppressor cells purified by negative selection produce higher amounts of PGE2 than adherent cells like monocytes and macrophages, and that these concentration levels are in the range of concentrations known to suppress a significant number of in vitro immunologic functions.